Supply Chain Management Practices, E-business Technologies, dan Kinerja Operasional Berpengaruh Meningkatkan Daya saing (Studi pada Perusahaan Manufaktur bersertifikat ISO 9000 di Indonesia) - Wullur, Magdalena (Universitas Brawijaya, Indonesia, 2009)
This research develops and tests the consistencies of the relation between supply chain management practice, e-business technologies, operational performance and competitiveness. The data for this research is obtained from 67 companies. The relations proposed in the framework of this research are tested using multiple linear regression analysis. The findings of this research shows the impact of supply chain management practice, e-business technologies and operational performance on improvement of competitiveness. Several variables, that is supply chain management practices, e-business technologies and operational performance have direct impact on the improvement of competitiveness. Lastly, it is found that supply chain management practice is the variable with the most dominant impact on competitiveness.